2012
DOI: 10.3109/01480545.2011.589846
|View full text |Cite
|
Sign up to set email alerts
|

Role of curcumin on chloroquine phosphate-induced reproductive toxicity

Abstract: The present study was conducted to screen the efficacy of curcumin against chloroquine phosphate (CQ)-induced reproductive toxicity in adult male Swiss albino mice. Animals were given oral doses of 100, 200, 300 mg/kg body weight (b.w.), and high dose of CQ (300 mg/kg b.w.) + curcumin (80 mg/kg b.w.) for 45 days. Animals of the withdrawal group were given high dose of CQ (300 mg/kg b.w.) for 45 days and, at day 46, were kept for another 45 days. Effects were observed on some key enzymes, such as alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The present results of CQP-group showed significant reductions in the final weight gains of body, testes, and epididymis, which are in agreement with the results of other researchers who hypothesize that long-term and/or shortterm administrations of CQP to experimental animals are associated with significant decreases in the weights of body (Mbajiorgu et al, 2008;Clewell et al, 2009), testes (Nicola et al, 1997Okanlawon and Ashiru, 1998;Ekaluo et al, 2008;Desai et al, 2012), and accessory sex organ, including epididymis (Nicola et al, 1997; Ekaluo et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results of CQP-group showed significant reductions in the final weight gains of body, testes, and epididymis, which are in agreement with the results of other researchers who hypothesize that long-term and/or shortterm administrations of CQP to experimental animals are associated with significant decreases in the weights of body (Mbajiorgu et al, 2008;Clewell et al, 2009), testes (Nicola et al, 1997Okanlawon and Ashiru, 1998;Ekaluo et al, 2008;Desai et al, 2012), and accessory sex organ, including epididymis (Nicola et al, 1997; Ekaluo et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Administration of CQP may disrupt the structural integrity of the testes and other organs via acting directly or indirectly on antioxidant status, leading to disturbance of oxidants/antioxidants balance with subsequent generation of multiple free radicals and development of oxidative stress as evidenced by significant decline in superoxide dismutase (a detoxifying enzyme catalyzes the dismutation of superoxide radical to hydrogen peroxide and oxygen) and remarkable depletion of hydrogen peroxide-decomposing enzymes such as catalase and glutathione peroxidase as well as increase in thiobarbituric acidreactive substances (byproduct of lipid peroxidation) due to accumulation of superoxide radical. Additionally, CQP may disrupt the functions of some testicular regulatory enzymes such as elevation of the acid phosphatase activity as well as depression of alkaline phosphatase, succinate dehydrogenase, and adenosine triphosphatase activities (Magwere et al, 1997;Desai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results further demonstrated the dose-dependent manner of the toxicity of medicines. 23,24 Hence, the effective and safe dosage needs to be determined for a clinical medicine. The clinical dose of Radix Dipsaci and Atractylodes macrocephala in ZYP is much lower than 2 g kg −1 d −1 and 3.54 g kg −1 d −1 , respectively, which further validates our results.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Side effects of treatment drugs Clinical studies have confirmed the effects of chloroquine on arrhythmia caused by prolonged QT intervals, conduction disturbances, and increased autonomy. 66,67 The clinical manifestations of chloroquine-induced cardiotoxicity are not specific, and one or more of the following abnormalities can appear 68,69 : (i) cardiac conduction disorders; (ii) ventricular premature beats, sometimes in the doublet or triplet, occasionally atrial flutter or atrial fibrillation; and (iii) a history of ventricular fibrillation and cardiac arrest in individual cases. The dosage of and indication for chloroquine were specified in the COVID-19 protocol (trial seventh edition), and it was pointed out that additional data on adverse cardiac reactions were needed.…”
Section: Oxygen Supply and Demand Imbalancementioning
confidence: 99%